A Case Study of Recipient Twin Surviving Complications of Twin‐to‐Twin Transfusion Syndrome. Issue 5 (18th October 2013) - Squires, Linda Sharee
Abstract Twin‐to‐twin transfusion syndrome (TTTS) has a high rate of mortality and morbidity. This article describes the clinical course of a recipient twin in a case of TTTS. The twin was on long‐term respiration support and survived two resuscitations, pneumothorax, chest tube placement, blood exchange, necrotizing enterocolitis and corrective surgery. This case demonstrates that the effective use of a collaborative, multidisciplinary care approach between two hospitals can result in a newborn surviving a severe case of TTTS.